Organizational Identity and Capability Development in Internationalization: Transference, Splicing, and Enhanced Imitation in Tesco’s US Market Entry - LOWE, Michelle (Institutional Knowledge at Singapore Management University, 2012)
Entry into international markets is a challenging process that fundamentally tests existing capabilities. During this entry process, capability gaps arise that need to be bridged to exploit the commercial opportunity and grow the business. Using a global retailer, Tesco plc, as a case study and employing grounded theory development techniques, we find that to achieve growth, two organizational attributes become critical—structural coherence of the firm’s capabilities and organizational identity. We identify three processes of capability development during market entry—transference, splicing and enhanced imitation. Further, actions and processes that maintain or adapt organizational identity serve as moderators of the relationship between these processes and the capability deployment and internalization necessary for entry into international markets. We discuss the study’s implications for theories of capability development, organizational identity and foreign market entry.